National Vaccination Shedule: Quality of Performance and Determining Factors - T. A. Platonova; A. A. Golubkova; E. S. Koltunova; S. S. Smirnova; V. V. Abdulvalieva; O. A. Kuznezova (Эпидемиология и вакцинопрофилактика)
Many issues concerning the organization of vaccination of the population in polyclinics still require improvement. The aim of the study is to assess the completeness and timeliness of vaccination of children in an outpatient setting and to identify factors affecting the adherence to vaccination of parents and medical staff. Materials and methods. The authors analyzed the history of child development and maps of preventive vaccinations of 631 children under 18 months of age to establish the completeness and timeliness of vaccinations against infections, approved by National immunization schedules. The authors analyzed the reasons for the lack of vaccinations and violations of the start and end of vaccination. To assess the population's attitude to vaccination, a survey of 865 parents and 1325 employees of medical organizations were conducted. In order to study the activity of discussion on the Internet issues related to vaccination, the number of records in the network on this topic and their content for 2007–2017 were analyzed. Results. The authors found that the coverage of children with vaccinations in the decreed age is insufficient and does not meet the requirements of National immunization schedules. The reasons for unvaccinated children in the maternity hospital were refusal of vaccination and medical contraindications (prematurity and low birth weight, respiratory failure, neonatal jaundice, HIV infection in the mother). In the clinic the leading causes of violation of the schedule of vaccination was temporary medical branches (the acute diseases), the late turnout at vaccination and refusals of immunization of parents. In assessing the attitude of parents to vaccination, the authors found that 79.3% of parents were positive, 6.4% – negative and 14.3% expressed doubts about the effectiveness and safety of vaccination. The main source of information was the opinion of health workers, among whom the survey revealed 187 people who are negative about vaccination. The opinion of relatives, friends and information received on the Internet were less authoritative. In assessing the monitoring data on the Internet, there was a significant increase in the number of people interested in and discussing the issues of vaccine prevention in social media, including their negative feedback. Conclusion. Authors recommend increasing the compliance of vaccine prophylaxis of medical workers, to form a positive attitude to vaccination among the population and to increase the coverage of vaccinations.